THE SIGNIFICANCE OF FORMING THE PROFIT OF COMMERCIAL BANKS IN THE DIGITAL ECONOMY - Usmanov P.Sh (PT ANTIS International Publisher, 2024)
The article presents the content of commercial banks' profit in the digital economy, the importance of its formation, and the analysis of influencing factors. Conclusions and suggestions on increasing the profit of commercial banks are also given in the work